IMPLEMENTATION OF THE GREAT CHILD (AHE) METHOD IN READING LEARNING AT AHE KARANG WOTAN: IMPLEMENTASI METODE ANAK HEBAT (AHE) DALAM PEMBELAJARAN MEMBACA DI AHE KARANG WOTAN - Wasis Wijayanto Ningsih; Shoimatul Magfiroh; Fina Faiqotul Ulya (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the development of AHE Karang Wotan, the community’s response to its presence, and the implementation of the Anak Hebat (AHE) Method in early reading instruction, including its challenges and solutions. This research employs a qualitative case study design with founders, tutors, students, and parents as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles & Huberman interactive model. Initial problems identified include students’ low reading ability, difficulty recognizing letters and syllables, and low motivation, worsened by limited facilities and minimal parental support. The findings show that the implementation of the AHE method through six stages brain exercise, remediation, module reading, enrichment, writing, and games effectively improves students’ early reading skills. AHE Karang Wotan has also grown significantly since its establishment in 2020, marked by increased student enrollment and strong community support. Challenges were addressed through tutor training, simple media utilization, and strengthened communication with parents.